Baroque tension and relaxation in contemporary Peruvian poetry: three cases (Revista de Crítica Literaria Latinoamericana, 2012)
This article analyzes the poetry of three authors whose works are among the most attractive of the last thirty years of Peruvian poetry. They have brought a rich complexity to their lyric tradition. That is the reason why their poetry has expanded the horizons of Hispanic poetry. Therefore, the purpose of this paper is to investigate an area of contemporary poetry—the works of José Morales Saravia, José Antonio Mazzotti and Róger Santiváñez—that without a doubt will mark some of the future paths of poetry in Spanish.
Keywords: Baroque; Neobaroque; Avant-garde; conversational poetry; influences